Deficiencies and loopholes: Clashing discourses, problems and solutions in Australian migration advice regulation. (September 2021) - Smith-Khan, Laura
In Australia, access to high-quality migration advice can often be crucial to obtaining a visa, and migration advisors have attracted ongoing scrutiny from policymakers, leading to successive inquiries and reviews. Such inquiries and the recommendations they produce are used to justify policy design and reform that can have significant impacts on a range of stakeholders, including of course, migration advisors and their clients. This article explores one such recent inquiry, completed in 2018. It adopts a critical discourse analysis to examine the way the inquiry's official report presents migration advisors, and how it frames the inquiry process itself. Finding that the report presents its recommendations as being based on evidence created by external stakeholder submissions, the examination goes on to explore to what extent this is actually the case. Through an examination of the 'textual travels' submissions undergo when incorporated in the report, the article finds that these texts are either transformed to support dominant discourses, or simply excluded. The article concludes that decision-making is inaccurately presented as a participatory, evidence-based process, thus legitimising particular policy decisions, and unfairly continuing to present migration advisors as problems requiring fixing.